2022
DOI: 10.1001/jamanetworkopen.2022.44343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient Characteristics on Uptake of Screening Using a Mailed Human Papillomavirus Self-sampling Kit

Abstract: ImportanceMailing human papillomavirus (HPV) self-sampling kits increases cervical cancer screening participation, but effects may differ across subpopulations. Subpopulation data can inform US health care system implementation.ObjectiveTo identify patient characteristics that modify effectiveness of a mailed kit intervention at increasing screening.Design, Setting, and ParticipantsThis was a secondary analysis of data from the Home-Based Options to Make Cervical Cancer Screening Easy (HOME) randomized clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Race and ethnicity at randomization were derived from self-reported EMR data; categories included American Indian or Alaska Native, Asian, Black or African American, Native Hawaiian or other Pacific Islander, White, other race and/or ethnicity (those selecting the other category were able to enter a free-text description; IRB approval did not allow reporting of individual-level data for all participants, so to maintain consistency across all participants in categorization of race and ethnicity, free-text entries were not reviewed or coded), and unknown race and/or ethnicity. 23 …”
Section: Methodsmentioning
confidence: 99%
“…Race and ethnicity at randomization were derived from self-reported EMR data; categories included American Indian or Alaska Native, Asian, Black or African American, Native Hawaiian or other Pacific Islander, White, other race and/or ethnicity (those selecting the other category were able to enter a free-text description; IRB approval did not allow reporting of individual-level data for all participants, so to maintain consistency across all participants in categorization of race and ethnicity, free-text entries were not reviewed or coded), and unknown race and/or ethnicity. 23 …”
Section: Methodsmentioning
confidence: 99%
“…In addition to differences in design and sociodemographic data, a major difference between the studies from the United States and Denmark and the present study is that the United States and Denmark studies include women only marginally overdue (e.g., 1 year overdue) for screening, while we restricted the trial to only include long-term non-attending women who had not attended screening for at least 10 years (i.e., who were at least 7 years overdue, indicating ignoration of at least four reminder letters for inclinic screening attendance). Winer et al 26 and Tranberg et al 25 thus report a higher participation rate among controls, a smaller total increase in participation for the women offered self-sampling relative to controls, and a higher proportion of in-clinic screening among T A B L E 4 (Continued) women offered self-sampling, compared to the present RCT. This limits the comparability to our study, especially for absolute effects because the baseline participation rates differ.…”
Section: Discussionmentioning
confidence: 39%
“…RCTs from Denmark and the United States, that also include women marginally overdue for screening, indicate little or no difference in sociodemographic inequalities between screening modalities. 25,26 To our knowledge, no RCT has addressed this issue among long-term non-attenders to cervical screening. Assessing interventions to improve screening compliance in this group is important because women who are long overdue for screening have relatively high cervical cancer incidence and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Our 2014-2017 HOME trial, 17 which was embedded in a US health care system, found that mailing HPV self-sampling kits to underscreened individuals increased screening by 9% over usual care (26% vs 17%), similar to international trials. 18,19 However, most individuals remained unscreened with low follow-up of HPV-positive results and patient understanding of testing. [18][19][20][21] As US health care systems introduce primary HPV screening with possible self-sampling, they need data to inform implementation.…”
mentioning
confidence: 99%
“…18,19 However, most individuals remained unscreened with low follow-up of HPV-positive results and patient understanding of testing. [18][19][20][21] As US health care systems introduce primary HPV screening with possible self-sampling, they need data to inform implementation. HPV self-sampling trials 22 have not specifically evaluated kit uptake among populations that are screeningadherent or have unknown screening history (where potential overscreening is a concern).…”
mentioning
confidence: 99%